Effects of Neuromuscular Training with and Without Kinesio-Tape on Pain, Range of Motion, Balance and Function in Footballer with Ankle Sprain - Memon, Aamir Gul; Chandran, Suriyakala Perumal; Annosha; Zakir, Tahira; Sulaman, Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To determine the effects of neuromuscular training with and without kinesio-tape on pain, range of motion, balance, and function in footballers with ankle sprain. METHODOLOGY: The randomized control trial was conducted at the Pakistan Sports Board, Lahore, from March to August 2023. The Squeeze and Talar Tilt Test purposefully identified thirty male football players who sustained grade I and II ankle sprains. Assigned to group A randomly, neuromuscular training alone (control n=15) and group B neuromuscular training with kinesio-tape (experimental n=15). Both groups performed neuromuscular training for 15–20 min for 4 weeks (three times per week), and after each session, Kinesio-tape was applied to the experimental group. Pain Intensity was evaluated with the Numerical pain rating scale (NPRS), range of motion (ROM) was measured by goniometer, dynamic balance status was assessed with the Star excursion balance test (SEBT), and ankle function was assessed with functional ankle ability measure (FAAM-Sports Subscale). RESULTS: After 4 weeks of intervention, both groups significantly improved all outcome measures. However, there was significant improvement (p<0.001) in intragroup analysis in all outcome measures after treatment in both groups with p< 0.001. Additionally, the between-group analysis revealed significantly more significant improvements in pain reduction, ROM, balance, and sports function in Group B compared to Group A. CONCLUSION: Both treatments significantly improved pain, range of motion (ROM), balance, and functional outcomes. However, the group receiving neuromuscular training supplemented with Kinesio Tape exhibited greater effectiveness in ankle sprain.